School relationship management with the community: analysis of program activity needs - Halim Purnomo; Firman Mansir; Tumin Tumin (Universitas Muhammadiyah Ponorogo, 2020)
This research was conducted aiming to describe the needs of schools, programming, division of executive tasks, the implementation of community relations activities, and evaluation of monitoring of school relations with the community in Kendal 1 State Middle School, Ngawi, East Java, Indonesia. This study uses a qualitative phenomenological design that is based on field observations, interviews, and documentation. This research produces an analysis of school needs following procedures, very specific program activities, appropriate goals and objectives as well as actions taken, division of tasks following program planning and implementation of activities running according to procedures, the direction of synergy coordination, motivation, communication and to provide guidance , monitoring and evaluation of school needs in improving the quality of learning needs to be improved.